2021
DOI: 10.3390/v13091728
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characterization of Human Bocavirus Detected in Croatian Children with Respiratory Infection

Abstract: Human bocavirus (HBoV) 1 is considered an important respiratory pathogen, while the role of HBoV2-4 in clinical disease remains somewhat controversial. Since, they are characterized by a rapid evolution, worldwide surveillance of HBoVs’ genetics is necessary. This study explored the prevalence of HBoV genotypes in pediatric patients with respiratory tract infection in Croatia and studied their phylogeny. Using multiplex PCR for 15 respiratory viruses, we investigated 957 respiratory samples of children up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In this study, in comparison with the same reference strain St1, we found the presence of only two substitutions and a low level of glycosylation of the capsid protein. Other studies have reported similar results regarding the VP1/VP2 protein [99][100][101] and amino acid substitutions in the order of 1 to 8 [102,103].…”
Section: Discussionsupporting
confidence: 66%
“…In this study, in comparison with the same reference strain St1, we found the presence of only two substitutions and a low level of glycosylation of the capsid protein. Other studies have reported similar results regarding the VP1/VP2 protein [99][100][101] and amino acid substitutions in the order of 1 to 8 [102,103].…”
Section: Discussionsupporting
confidence: 66%
“…In the Suzhou area, HBoV is mainly prevalent in summer and autumn. In Brazil and Croatia, the highest detection rates were recorded in winter ( 7 , 8 ). Peaks in the HBoV prevalence were observed in summer and autumn in 2017, 2018, and 2019 in this study, whereas HBoV detection rates were significantly lower in summer and autumn 2020 than in previous years, with peaks observed in winter 2020 and spring and summer 2021.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, a recent meta-analysis by Polo et al, including 35 studies on 32,656 subjects from 16 countries, showed that HBoV prevalence varied from 2.0% to 45.69% with a pooled estimate rate of 9.57% [ 29 ]. More recently, a retrospective analysis through PCR screening on an English cohort of children with RTIs identified a 9% prevalence of HBoV1 [ 20 ]; in Croatia, a recent study on 957 children hospitalized with RTIs revealed a prevalence of 7.6% [ 30 ], and, in Norway, the prevalence reached 12% in a study by Christensen et al [ 31 ]. The lowest rates were found by Pinana in Spain (3%) [ 8 ], and Kantola et al in Finland (2%) [ 32 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The mixed viral infection rate is relatively high in most studies on NP swab samples, with rates of 38.3% in Australia [ 15 ], 47% in Denmark [ 86 ], 51.6% in China [ 4 ], 54% in Panama [ 87 ], around 75% in Italy [ 88 ], Spain [ 8 , 75 ], UK [ 20 ], and Norway [ 2 ], up to 80% in Saudi Arabia [ 10 ], 82.2% in Croatia [ 30 ], and 84% in Gabon [ 89 ]. Guido et al estimated the rate of HBoV co-infections with other viruses to be 52.4% (respiratory infections) and 46.7% (gastrointestinal infections) [ 24 ].…”
Section: Co-infectionsmentioning
confidence: 99%
See 1 more Smart Citation